PRINCIPLES OF DEVELOPING THE SENSE OF SPIRITUAL SOLIDARITY AMONG YOUTH - M. B. Rahmonov (Modern American Journals, 2025)
The article analyzes the main principles of developing a sense of spiritual solidarity among youth, its significance in the process of education and upbringing, and presents effective pedagogical approaches to strengthening it within educational institutions.
Keywords: Solidarity, spirituality, youth, education, upbringing, unity, cooperation, values, person, community.